Hispolon induces apoptosis in oral squamous cell carcinoma cells through JNK/HO‐1 pathway activation. Issue 9 (27th March 2023) - Yang, Wei‐En; Chen, Yi‐Tzu; Su, Chun‐Wen; Chen, Mu‐Kuan; Yeh, Chia‐Ming; Chen, Yen‐Lin; Tsai, Meng‐Ying; Yang, Shun‐Fa; Lin, Chiao‐Wen
Abstract: Oral squamous cell carcinoma (OSCC) has a high recurrence rate and poor prognosis. Hispolon, a polyphenolic compound with antiviral, antioxidant, and anticancer activities, is a potential chemotherapy agent. However, few studies have investigated the anti‐cancer mechanism of hispolon in oral cancer. This present study used the cell viability assay, clonogenic assay, fluorescent nuclear staining, and flow cytometry assay to analyse the apoptosis‐inducing effects of hispolon in OSCC cells. After hispolon treatment, the apoptotic initiators, cleaved caspase‐3, −8, and − 9, were upregulated, whereas the cellular inhibitor of apoptosis protein‐1 (cIAP1) was downregulated. Furthermore, a proteome profile analysis using a human apoptosis array revealed the overexpression of heme oxygenase‐1 (HO‐1) by hispolon, which was determined to be involved in caspase‐dependent apoptosis. Moreover, cotreatment with hispolon and mitogen‐activated protein kinase (MAPK) inhibitors revealed that hispolon induces apoptosis in OSCC cells through activation of the c‐Jun N‐terminal kinase (JNK) pathway and not the extracellular signal‐regulated kinase (ERK) or p38 pathway. These findings indicate that hispolon may exert an anticancer effect on oral cancer cells by upregulating HO‐1 and inducing caspase‐dependent apoptosis by activating the JNK pathway.